Skull Base Chondrosarcomas: Surgical Treatment and Results. (December 2013) - Sbaihat, Ahmad; Bacciu, Andrea; Pasanisi, Enrico; Sanna, Mario
Objectives: We describe our experience in the management of patients with skull base chondrosarcoma, an uncommon neoplasm of the skull base. Methods: Thirteen cases of surgically treated skull base chondrosarcomas were identified. The patients' follow-ups ranged from 7 to 86 months (mean, 47 months). Results: The most common tumor locations were the jugular foramen (5 cases), the petrous apex (3 cases), and the petroclival region (3 cases). An infratemporal fossa type A approach was performed in 2 cases, and 2 patients underwent an infratemporal fossa type B approach. Two patients underwent a transotic approach, 1 patient underwent a petro-occipital transsigmoid approach, and a petro-occipital transsigmoid approach combined with a transotic approach was chosen in 1 case. One patient underwent an infratemporal fossa type C approach combined with a transotic approach, and 2 patients underwent an infratemporal fossa type B approach combined with a transotic approach. One patient underwent an infratemporal fossa type B approach combined with a transzygomatic approach, and the last patient underwent a transmastoid approach. Gross total tumor removal was achieved in all patients. Postoperative radiotherapy was performed in 7 cases. The most common complications were lower cranial nerve deficits. Two patients experienced recurrences, 36 months and 6 years after surgical removal. Conclusions: We believe that the primary treatment for chondrosarcomas of the skull base is gross total surgical resection. We usually do not recommend radiotherapy as the primary treatment for patients with skull base chondrosarcomas; however, radiotherapy may be considered as an alternative primary treatment in selected cases in which there are serious medical contraindications to surgery, as well as in elderly patients. We reserve postoperative radiotherapy for patients with histologically aggressive tumors (grade II or III), as well as for cases of subtotal resection or recurrent tumors.